Book Review: George E. DEMACOPOULOS, Colonizing Christianity: Greek and Latin Religious Identity in the Era of the Fourth Crusade, New York: Fordham University Press, 2019 - KINLOCH, Matthew (Byzantina Symmeikta, 2019)
George E. DEMACOPOULOS, Colonizing Christianity: Greek and Latin Religious Identity in the Era of the Fourth Crusade, New York: Fordham University Press, 2019, pp. v + 184. ISBN 9780823284429